2019
DOI: 10.3390/ijerph16214207
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator and/or Moderator Role of Complexity of Knowledge about Healthy Eating and Self-Regulated Behavior on the Relation between Family’s Income and Children’s Obesity

Abstract: Childhood obesity rates have been increasing over the years and is considered one of the most serious public health problems of the century. Low socioeconomic status has been associated with a higher body mass index. However, the pathways underlying this complex relationship are poorly understood. This study aimed to evaluate the possible mediation and/or moderation effects of complexity of knowledge about healthy eating, and self-regulation processes towards healthy eating, in the association between family’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
4
14
0
1
Order By: Relevance
“…In contrast, a recent survey among 600 Spanish adults reported that most of the participants maintained vegetable and fruit consumption during the first 5 confinement weeks, although these results might have changed after the whole confinement period ( 50 ). Also, lower food away from home consumption was linked to changes in diet quality (i.e., less added sugars and added fats, and more fiber consumption) ( 51 ), although, for this specific and unprecedented context differences regarding usual eating habits and socioeconomic family status (i.e., higher family socioeconomic status usually lead to healthier eating habits), self-regulating behaviors and knowledge might play an important role ( 52 ). Also, school canteen deprivation could influence the fruit and vegetable consumption since that has observed to worsen healthy habits concerning diet ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a recent survey among 600 Spanish adults reported that most of the participants maintained vegetable and fruit consumption during the first 5 confinement weeks, although these results might have changed after the whole confinement period ( 50 ). Also, lower food away from home consumption was linked to changes in diet quality (i.e., less added sugars and added fats, and more fiber consumption) ( 51 ), although, for this specific and unprecedented context differences regarding usual eating habits and socioeconomic family status (i.e., higher family socioeconomic status usually lead to healthier eating habits), self-regulating behaviors and knowledge might play an important role ( 52 ). Also, school canteen deprivation could influence the fruit and vegetable consumption since that has observed to worsen healthy habits concerning diet ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, both parental guidance and example can strongly influence children's and adolescent behaviors regarding diet, screen, and physical activity habits ( 55 , 56 ), which, in turn, could be also influenced by socioeconomic variables such as education and income (i.e., higher education or higher income may lead to healthier HRB) ( 52 , 57 ). Health complications for children and adolescents derived from prolonged confinement or repeated viruses' outbreaks might comprise a higher fat percentage, lower bone mineral density, lower motor competence, higher blood pressure, and higher socio-emotional behavior problems later, among others ( 58 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these interventions focused on transmitting nutritional knowledge about healthy food, especially emphasizing on increased consumption of fruits and vegetables, and targeting specific behaviors, such as unhealthy eating habits and lack of physical activity (e.g., [ 14 ]). However, research shows that beliefs about healthy eating have a stronger influence on eating behavior than factual knowledge about food [ 17 ] and that providing knowledge about healthy eating only has influence on weight when combined with the promotion of self-regulation competences [ 18 ]. This suggests that the traditional approach of simply conveying knowledge on healthy eating may not be the optimal one.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, SR has started to receive attention as a key predictor of a variety health-related and wellbeing outcomes. For instance, poor SR appears to be a predictor of weight gain, especially in adolescence [ 18 , 20 , 31 ]. Several studies have successfully implemented self-management programs among individuals with various health conditions, such as heart disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%